Aquisição de grandezas elétricas : definição de arquitetura, método e validação em protótipo - Figueiredo, José Antônio Oliveira de (2016)
This work, describes an architecture and methodology developed to properly acquire electric current and electric potential on installations. The architecture is composed by modules which are: acquisition, processing and visualization. The Acquisition module is based on Arduino platform and uses electromagnetic sensors; the processing module performs data extraction, data processing and data storage; lastly, the visualization module is an interface to the user takes a view about collected informations. The system was implemented and validated in a prototype called Monitor of energy consumption, electric current and electric potential (acronym MCCT in portuguese). This validation was made on test bench, where various common equipments were turned on (with several combinations), while his electrical data was acquired and registered. When this prototype is compared to other commercial equipment used to collect/analyze electrical power, an important differential worth mentioning is the ability to storage values of electrical current and potential waveforms. This is done in each detection electric current change, indicating that some equipment was turned on or turned off. That way, the MCCT is ready to several futures research works. The main results are the development of a platform for the acquisition of electrical quantities, validated by a prototype, and also an architecture and method capable of identifying events in electrical installations. During the course of work, were made several experiments. These experiments were assembled in a book called Cookbook for acquiring electrical current alternating and electrical potential alternating with Arduino. The purpose of the book is to be a teaching guide for new researchers working on acquisition of electrical values. Finally, this work opens up a range of opportunities to work on electrical values acquisition, in development of new applications and, of course, the improvement of the presented method